Sentinel Lymph Nodes Mapping in Cervical Cancer a Comprehensive Review. Issue 1 (1st January 2016) - Diab, Yasser
Abstract : Objective: A comprehensive literature search for more recent studies pertaining to sentinel lymph node mapping in the surveillance of cervical cancer to assess if sentinel lymph node mapping has sensitivity and specificity for evaluation of the disease; assessment of posttreatment response and disease recurrence in cervical cancer. Materials and Methods: The literature review has been constructed on a step wise study design that includes 5 major steps. This includes search for relevant publications in various available databases, application of inclusion and exclusion criteria for the selection of relevant publications, assessment of quality of the studies included, extraction of the relevant data and coherent synthesis of the data. Results: The search yielded numerous studies pertaining to sentinel lymph node mapping, especially on the recent trends, comparison between various modalities and evaluation of the technique. Evaluation studies have appraised high sensitivity, high negative predictive values and low false-negative rate for metastasis detection using sentinel lymph node mapping. Comparative studies have established that of all the modalities for sentinel lymph node mapping, indocyanine green sentinel lymph node mapping has higher overall and bilateral detection rates. Corroboration of the deductions of these studies further establishes that the sentinel node detection rate and sensitivity are strongly correlated to the method or technique of mapping and the history of preoperative neoadjuvant chemotherapy. Conclusions: The review takes us to the strong conclusion that sentinel lymph node mapping is an ideal technique for detection of sentinel lymph nodes in cervical cancer patients with excellent detection rates and high sensitivity. The review also takes us to the supposition that a routine clinical evaluation of sentinel lymph nodes is feasible and a real-time florescence mapping with indocyanine green dye gives better statistically significant overall and bilateral detection than methylene blue.